Artificial Intelligence, Cybersecurity, and Human Trafficking Networks - Triplett, William J. (Cybersecurity and Innovative Technology Journal, 2024)
This study aimed to examine the role of artificial intelligence (AI) in dealing with human trafficking by analyzing social networks. Human trafficking is a global concern that exists in the anonymity of social connections and online platforms. There are important transformative tools that facilitate the identification and disruption of trafficking networks, including AI techniques like natural language processing, social network analysis, and machine learning.  The study tests AI applications, ethical considerations, and cybersecurity measures that importantly safeguards data integrity and promotes the efficacy of AI-driven systems. The outcomes of the study show the potential of AI in pattern recognition, network mapping, and predictive analytics to support law enforcement and advocacy groups.